The Effect of Whatsapp-Based Health Education on Improving Maternal Health Literacy in Stunting Prevention at Dengilo Health Center - Verrawaty Amelia Padunggala; Hartati Inaku; Rini Asnawati (Universitas Muhammadiyah Palu, 2026)
The Influence of Whatsapp-Based Health Education on Improving Maternal Health Literacy in Stunting Prevention at the Dengilo Health Center, Pohuwato Regency, guided by Hartati Inaku as chairman and Rini Asnawati as a member. Stunting is still a major problem for infants and children under the age of 2 in Indonesia. This condition must be resolved immediately for the achievement of a healthy, intelligent, and productive Indonesian golden generation, as well as the success of achieving sustainable development goals. (Perpres, 2021). The purpose of the study was to determine the effect of whatsapp-based health education on increasing maternal health literacy in preventing stunting in the working area of the Dengilo Health Center. Quantitative correlation with the Pre-Experiment research method with the type of one group pre-test and posttest design The quantitative correlation research sample in this study was mothers who had stunted children and the risk of stunting as many as 50 respondents. The Effect of WhatsApp-Based Health Education on Increasing Maternal Health Literacy in Stunting Prevention After data tabulation with spss using the paired sample t test obtained a sig.tailed value of 0.000 < 0.05 which means that there is an effect of providing education through WhatsApp on increasing maternal health literacy in stunting prevention at the Dengilo Health Center, Pohuwato Regency. Conclusion There is an influence between whatsapp-based health education and maternal health literacy in stunting prevention at the Dengilo health center, Pohuwato Regency. It is expected that the Puskesmas will use WhatsApp media in an ongoing manner as one of the health education strategies in an effort to increase maternal health literacy and prevent stunting in the work area of the Puskesmas.